Female school principals: perceptions of leadership in a male dominated education environment - Mwingi, Mweru P (Rhodes University, Faculty of Education, Department of Education, 2000)
Many well-known studies on leadership have ignored the perspective of women yet bear an emphasis on the importance of portraying leadership in its entirety. This would mean that all leadership perspectives are included and that leaders are allowed to speak for themselves and about themselves. It is this connection I have sought to establish how women perceive leadership by relating the experiences of four women in school principalship. I have used a factual questionnaire to establish the background of each one but, it is the in-depth interviews that yield the leadership perceptions. Borrowing from phenomenological procedures, the leadership experiences are related as Natural Meaning Units (NMUS) whereby all prior knowledge and possible bias are bracketed out. Reinforced by their journal entries, it is only the voice of the women that is heard. My study reinforces the observation of researchers and feminist scholars that women leaders are not only marginalised but also viewed from a perspective that is not their own. From the study, however, the one element about leadership that emerges as unique is the functioning of transformational leadership elements among women leaders in educational set-ups that are inherently traditional, bureaucratic and hierarchical. This is significant because there is an indication that women leaders are inclined to transformational leadership because it favours their feminine qualities. There is also evidence that school principals can embrace leadership diversity and finally, that leadership and the structures of leadership operation are not developed from without but from within the person of the leader and this is an incorporation of their vision and beliefs. In the context of South Africa, this study should be of potential significance because of the change that is taking place in the development and training of school principals.
Keywords: Uncatalogued